From Foundation to Acceleration: An Analysis of Indonesia's Two-Decade PPP Journey - Ade Hendraputra (Pusbindiklatren Bappenas, 2026)
Indonesia faces a substantial infrastructure gap, making Public-Private Partnerships (PPPs) critical to address financing challenges. This study discusses Indonesia's PPP framework evolution across two decades (2005-2024), exploring why progress differed markedly between the